Vitamin D Status and VDR Genotype in NF1 Patients: A Case-Control Study from Southern Brazil - Larissa Souza Mario Bueno; Clévia Rosset; Ernestina Aguiar; Fernando de Souza Pereira; Patrícia Izetti Ribeiro; Rosana Scalco; Camila Matzenbacher Bittar; Cristina Brinckmann Oliveira Netto; Guilherme Gischkow Rucatti; José Artur Chies; Suzi Alves Camey; Patricia Ashton-Prolla (International Journal of Endocrinology)
Neurofibromatosis type 1 (NF1) patients are more likely to have vitamin D deficiency when compared to the general population. This study aimed to determine the levels of 25-OH-vitamin D [25(OH)D] in individuals with NF1 and disease-unaffected controls and analyze FokI and BsmI VDR gene polymorphisms in a case and in a control group. Vitamin D levels were compared between a group of 45 NF1 patients from Southern Brazil and 45 healthy controls matched by sex, skin type, and age. Genotypic and allelic frequencies of VDR gene polymorphisms were obtained from the same NF1 patients and 150 healthy controls. 25(OH)D deficiency or insufficiency was not more frequent in NF1 patients than in controls (p=0.074). We also did not observe an association between FokI and BsmI VDR gene polymorphisms and vitamin D levels in NF1 patients, suggesting that their deficient or insufficient biochemical phenotypes are not associated with these genetic variants. The differences between the groups in genotypic and allelic frequencies for FokI and BsmI VDR gene polymorphisms were small and did not reach statistical significance. These polymorphisms are in partial linkage disequilibrium and the haplotype frequencies also did not differ in a significant way between the two groups (p=0.613).